HISTOLOGY AND HISTOCHEMISTRY OF LIMBIC HIPPOCAMPUS IN THE INDIAN BUFFALOES - A. Kumaravel; Geetha Ramesh; S. Rajathi; S. Muthukrishnan (Indian Journal of Veterinary and Animal Sciences Research, 2024)
The brain samples were collected from 10 calves and 10 adult Indian buffaloes. Routine histological and histochemical processing and sectioning were done. The hippocampus was a curved elevation, lying immediately ventral to the splenium of the thalamus. Longitudinal section showed the ependyma, the alveus, the stratum oriens, the stratum pyramidale, the stratum radiatum, the stratum lacunosum and the stratum moleculare from above downwards. The prominent layer was the stratum pyramidale, composed of pyramidal cells in 2-3 rows. The four fields of the cornu ammonis, (CA1, CA2, CA3 and CA4) were identified based on the sizes of the pyramidal cells and their dendritic arborizations, both in the calf and in the adult. The presence of mucopolysaccharides was recorded.